1995
DOI: 10.1139/o95-033
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of pancreatic exocrine enzymes by islet transplantation in diabetic rats

Abstract: In an effort to evaluate the effectiveness of islet transplantation in correcting exocrine dysfunction, young male Lewis rats were made diabetic by i.v. streptozotocin injection. Diabetes status was confirmed by decrease in insulin and increase in blood glucose and glycosylated hemoglobin levels. Pancreatic islets were isolated from age-matched control syngeneic rats by collagenase digestion followed by purification through a Ficoll gradient. Islets (approximately 1200) were grafted to the liver by intraportal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…We found reduced amylase expression in acinar cells of STZ-injected mice. Similar observations were reported in STZ-injected rats, in which the mRNA level of pancreatic amylase was decreased (10,13). However, this reduction of amylase expression exerted only a small, if any, effect on transdifferentiation capacity of acinar cells.…”
Section: Discussionsupporting
confidence: 86%
“…We found reduced amylase expression in acinar cells of STZ-injected mice. Similar observations were reported in STZ-injected rats, in which the mRNA level of pancreatic amylase was decreased (10,13). However, this reduction of amylase expression exerted only a small, if any, effect on transdifferentiation capacity of acinar cells.…”
Section: Discussionsupporting
confidence: 86%
“…3). It has been reported that pancreatic amylase is regulated by several factors, such as insulin, [10][11][12][13][14][15] glucocorticoid, 26,27) and cholecystokinin (CCK). 25) Reduction of amylase by a low carbohydrate diet or a high protein diet has been explained by lowered insulin secretion with a reduction in dietary carbohydrate ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…Although we also examined changes in insulin levels in the early stages of feeding, the relation of insulin levels in the early feeding period to pancreatic amylase activity cannot be determined due to large variation in insulin levels (data not shown). Because exogenous insulin [10][11][12] and endogenous insulin from transplanted B cells 13) restored amylase mRNA levels to a great extent in diabetic rats, insulin is probably important for the maintenance of amylase activity. But it has also been reported that exogenous insulin does not stimulate pancreatic amylase induction in normal rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of recent studies have described that basal insulin levels are extremely essential for the mRNA expression and secretion of a-amylase in normal and diabetic rats (Lee et al, 1995;Hashimoto et al, 2004). It has also been suggested that leucine can improve tissue protein synthesis through the insulin-dependent (Rogero and Tirapegui, 2008) and insulin-independent (Lynch et al, 2002) mechanisms.…”
Section: Plasma Insulinmentioning
confidence: 99%